ANALISA KEBUTUHAN AIR BERSIH PADA DAERAH KEK MANDALIKA BERDASARKAN PERTUMBUHAN PENDUDUK DAN LAJU WISATAWAN - SOFIYANDI SOFIYANDI; KUSMIANTI KUSMIANTI; ARIANTO ARIANTO; NI PUTU TITIN SUARTINI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
Fresh water is one of most important and basic needs to support human life. With the growth of the population and the increasing rate of tourists in the KEK Mandalika area in Pujut District, there will be more and more need for fresh water every year.The purpose of this study is to determine the need and availability of fresh water for the KEK Mandalika area in Mertak Village and Kuta Village in Pujut District. The results of the analysis shows that the population growth rate in 2027 in Mertak Village is 9,926 people and in Kuta Village it is 10,131 people.In this study, the total water needs are obtained at 131,992 lt/dt and the current water source is 481 lt/dt. Thus, the availability of water is surplus to water needs in Mertak Village and Kuta Village in the KEK Mandalika area, Pujut District and the needs of the ITDC until 2027